Green operations strategy of a luxury car manufacturer. Issue 1 (2nd January 2016) - Nunes, Breno; Bennett, David; Shaw, Duncan
ABSTRACT: This paper investigates the strategic environmental decisions of a luxury car manufacturer. Through case study research, the investigation sheds light on why and how the company is adopting green technologies. Being pressured by different stakeholders to become greener, luxury car manufacturers carry significant opportunities for environmental improvement given the nature of their manufacturing processes and products. Because of their low-volume production, manufacturers may be able to increase output and still reduce overall emissions when compared to high-volume manufacturers. In the case study company this was found to be possible only because of new ideas brought by a change in ownership. Luxury manufacturers may also be a test-bed for the development and experimentation of green technologies as part of a strategic approach to environmental initiatives. This paper contributes to the fields of green technology adoption and operations strategy in automotive manufacturing groups.